European founds and its using for tourist and recreation infrastructure development in region. The case of Słupsk Poviat - Parzych, Krzysztof (Journal of Education, Health and Sport, 2017)
The aim of this article was an analysis of the using of the european founds for tourist infrastructure development in tourist region. As case of study poviat Słupsk was used. Analysis of the using of european founds in Słupsk poviat was used from 2003 to 2006 year and from 2006 to 2013 year. As a source of the material data of the Ministry of the Regional Development was used. The data show the most of the founds in the poviat was used in Słupsk, only small part of them was used form tourist development Analysis show european founds are very important factor of economic development in Słupsk poviat.